Identification of alternative statistics for analyzing ordinal data in guidance and counseling research - Rohimah, Siti; Ahman, Ahman; Raudotussolehah, Rika Mia; Mudrikah, Syifa; Aqra, Naila Rumaisha (Universitas Islam Negeri Raden Intan Lampung, 2024)
In analyzing the needs of the counselee, an assessment is needed. Needs assessment cannot be separated from statistical tests as a tool. The purpose of conducting research is to find alternative statistical methods for analyzing ordinal data in Guidance and Counseling research. This includes a number of important elements which overall aim to improve the quality, validity and reliability of future Guidance and Counseling research results. In Guidance and Counseling research, identifying appropriate alternative statistics for analyzing ordinal data is important. This is because ordinal data often appears in the form of rating scales, questionnaires and subjective scales. Some alternative statistics that can be used include the Mann-Whitney U Test, Wilcoxon Matched Pairs Signed Rank Test, Kruskal-Wallis On-Way Analysis of Variance Test, and Friedman Analysis of Variance Test. This research is a type of literature study or literature study. Literature studies are intended to search for relevant theoretical sources that suit the research topic being discussed. The use of alternative statistics can be applied and developed based on research findings to analyze ordinal data in the context of guidance and counseling. By using appropriate alternative statistics, researchers can analyze ordinal data accurately and obtain meaningful findings in Guidance and Counseling research.